2015
DOI: 10.1308/003588415x14181254790400
|View full text |Cite
|
Sign up to set email alerts
|

National survey on endoscopy training in the UK

Abstract: This survey highlights marked disparities between surgical and gastroenterology trainees in both aiming for and achieving accreditation in endoscopy. Without changes to the delivery and provision of training as well as clarification of the role of endoscopy training in a surgical training programme, future surgeons will not be able to perform essential endoscopic assessment of patients as part of their management algorithm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 5 publications
1
18
0
Order By: Relevance
“…Although these posts were devised to support research activity and trainees going OOP, trainees acquire endoscopic experience that is often not achieved through in-programme activity alone. Supporting this assertion is a recent survey evaluating endoscopic training in the UK 12. Findings from this study suggest that although gastroenterology trainees had favourable experiences compared with surgical trainees, only 91.3%, 68.6% and 73.0% were expected to achieve the Joint Advisory Group certification requirements of 200 procedures in gastroscopy, flexible sigmoidoscopy and colonoscopy (provisional) at the time of completion of training (CCT).…”
Section: Introductionmentioning
confidence: 82%
“…Although these posts were devised to support research activity and trainees going OOP, trainees acquire endoscopic experience that is often not achieved through in-programme activity alone. Supporting this assertion is a recent survey evaluating endoscopic training in the UK 12. Findings from this study suggest that although gastroenterology trainees had favourable experiences compared with surgical trainees, only 91.3%, 68.6% and 73.0% were expected to achieve the Joint Advisory Group certification requirements of 200 procedures in gastroscopy, flexible sigmoidoscopy and colonoscopy (provisional) at the time of completion of training (CCT).…”
Section: Introductionmentioning
confidence: 82%
“…It previously has been reported that the majority of gastroenterology trainees in the UK felt it was likely that they would become accredited in both upper and lower gastrointestinal endoscopy prior to achieving CCT whereas only half of surgeons felt this was achievable for colonoscopy. Similarly, the proportion of surgical trainees who had already achieved certification was much lower than that for gastroenterology trainees at the time of the survey . The 2016 British Society of Gastroenterology (BSG) trainees’ survey discussed important issues facing the delivery of endoscopy training in the UK .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years there has been a perception that JAG certification in colonoscopy is increasingly hard to achieve for surgical trainees . In support of this view, a national survey on endoscopy training in the UK showed a significantly higher proportion of gastroenterologists than surgeons achieving accreditation in colonoscopy (66.7% vs 1.4%) and flexible sigmoidoscopy (33.3% vs 3.0%) . The most obvious explanation is the lack of sufficient training time and exposure to endoscopy within surgical training.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, 100% of general surgeons indicated willingness to use endoscopy and complained about inadequate training opportunities. A study by Jones et al found that 38% of general surgeons in the UK performed endoscopy versus 60% of gastroenterologists, and reported that general surgeons should gain accreditation for endoscopy [ 16 ]. In Turkey, no institution currently provides routine accreditation in endoscopy training in a general surgery residency.…”
Section: Discussionmentioning
confidence: 99%